Antimicrobial Activity of Acetone Extracts of Thavetia peruviana - Naidu, M A (International Journal of Pharmaceutical & Biological Archive, 2016)
Thevetia peruviana are potentially lethal plants after ingestion. The plants is common toxicological emergency in tropical and subtropical parts of the world and international self-harm, using T. peruvian is prevalent in south Asian countries, especially in India and Sri Lanka. All parts of these plants are toxic, and contain a variety of cardiac glycosides including nerifolin, thevetin A, Thevetin B and oleandrin. Ingestion of oleander results in nausea, vomiting, abdominal pain, diarrhoea, disrhythmias and hyperkailemia in most cases; clinical management of poisoning by either N. oleander or T. peruviana involves administration of activated charcoal and supportive care. This article compiles all the information related to Thevetia peruviana.